Comparison of the mechanical properties of four-layer epoxy composite reinforced with natural jute fibers and symmetrical e-glass synthetic fibers - Rahmat Firman Septiyanto; Hanif Akbar Dawam Abdullah; Isriyanti Affifah; Fatah Sulaiman; Syamsul Hidayat; Rahmat Awaludin Salam (Universitas Sultan Ageng Tirtayasa, 2020)
ABSTRACTResearch that produces environmentally friendly products continues to be developing. Research related to the natural fiber jute material and epoxy matrix has done. Epoxy composite jute empowered do with the preparation of symmetry with four layers of fiber volume fraction of 27.89% and composite epoxy e-glass Fiber empowered four balance with 28.86% fiber volume fraction. Mechanical testing is done via Drag test to determine the tensile strength and stretch. From the analysis, it's finding that the tensile strength of the symmetry jute fiber reinforced epoxy tensile strength was 48,378 MPa, and the strain was 11,998%. Meanwhile, the tensile strength and pressure in empowered epoxy e-glass fiber symmetry of four layers, each for 95.516 MPa and 7.7032%. Characterization has also been carried out through SEM testing. The results show that e-glass fiber fractures can still be seen as regular and tend to be straight and flat rods compared to symmetrical fiber-reinforced jute composite epoxy composites whose fibers are irregular. So that shows that the strength of the epoxy composite reinforced e-glass fiber is very large compared to the strength of the four-layer jute fiber-reinforced epoxy composite symmetry.